Efficacy and safety of methotrexate in alopecia areata - Mariana Hammerschmidt; Fabiane Mulinari Brenner (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: Alopecia areata is a chronic disorder of the hair follicles and nails, of unknown etiology, with clear autoimmune components and genetic factors. Several therapeutic options have been suggested; however, no treatment is able to modify the disease course. Methotrexate is an immunosuppressant used in various dermatoses and recently introduced as a therapeutic option for alopecia areata. OBJECTIVES: To evaluate the efficacy and safety of methotrexate in alopecia areata. METHODS: In a retrospective, non-controlled study, we evaluated 31 patients with alopecia areata in current or prior treatment with methotrexate to assess the therapeutic response according to sex, age, pattern of alopecia areata, disease duration, cumulative dose of methotrexate, use of systemic corticosteroids or other treatments, and drug safety. RESULTS: Regrowth greater than 50% was observed in 67.7% of patients, with the best responses observed in those with <5 years of disease progression (79%), age over 40 years (73.3%), male patients (72.8%), cumulative dose of methotrexate 1000-1500 mg, and multifocal alopecia areata (93%). Among patients receiving systemic corticosteroids in combination with methotrexate, 77.3% had greater than 50% regrowth, compared with 44.4% in those who used methotrexate alone. The therapeutic dose ranged from 10-25 mg/week. No patient had serious adverse effects. Relapse was observed in 33.3% of patients with more than 50% regrowth. CONCLUSION: Methotrexate appears to be a promising and safe medication for the treatment of severe alopecia areata when used alone or in combination with corticosteroids.